Proposisi dalam Kicauan Twitter Anak Usia Remaja: Suatu Tinjauan Psikolinguistik - Nicky Rosadi (LITERATUS, 2021)
This study aims to determine the propositions contained in the Twitter tweets of teenagers. This study uses a qualitative descriptive analysis method with content analysis. The object of this research is Twitter tweet text written by teenagers. The instrument used in this study was the researcher himself who was assisted by the data analysis table with the criteria for analysis through three observations, namely the structure of the proposition, the relation of meaning between the predictor and the argument, and the division of the roles of each argument. Based on the results of the analysis, it was found that 52.31% of the structure of the P + N1 proposition, 50.77% of the predictors had meaningful actions, and 25.86% of the arguments played the main role. Thus, it can be concluded that the structure of the proposition that is widely used in the tweets of teenagers is the core predication structure, with predicator’s meaningful actions, and arguments that play the main role.